Resiliensi Psikospiritual pada Mahasiswa Broken Home (Psychospiritual Resilience among Students from Broken Homes) - Yani Husain At Thohari, Muhammad; Balgies, Soffy (Happiness: Journal of Psychology and Islamic Science, 2025)
This study aims to examine the forms, processes, and contributing factors of psychospiritual resilience among students from broken home backgrounds in the Tasawuf and Psychotherapy Program at UIN Sunan Ampel Surabaya. This research employed a qualitative research approach with a phenomenological design. The participants consisted of 10 students selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using thematic analysis. The findings reveal that students’ psychospiritual resilience is developed through emotional regulation, self-control, optimism, and consistent spiritual practices such as dzikir, prayer, and self-reflection. Social support from peers, the campus environment, and religious communities plays a significant role in strengthening students’ resilience. The integration of Tazkiyah al-Nafs and Salutogenesis theories indicates that psychospiritual resilience functions not only as an adaptive coping mechanism but also as a transformative process that fosters psychological balance and spiritual growth among students from broken home families.